Author Correction: Even-denominator fractional quantum Hall states at an isospin transition in monolayer graphene. Issue 12 (December 2018) - Zibrov, A.; Spanton, E.; Zhou, H.; Kometter, C.; Taniguchi, T.; Watanabe, K.; Young, A.
In the version of this Article originally published, the sketch of 'PSP' in Fig. 1a was incorrect; it has now been replaced. Please see the correction note to compare the original and corrected figure.